Direito fundamental à saúde: dever do Estado na concessão dos planos e seguros privados - Queiroz, Isabel Cristina Arriel de (2017)
The health system in Brazil is sick and so, with this work, I intend to demonstrate that the chaos experienced in the public health area is caused by the system manager himself, if the rulers and true administrators of the Brazilian State. The constitutional articles on health, I could verify that the problem stems from the significant interpretation awry State to art.199 and its §º1 the Constitution of 1988. The aforementioned article allows the participation of private initiative, with the state supplement the System services Unified Health, on account, risk and the state itself guideline. When comparing the model adopted in public health in Canada state can clearly see that, in practice, such a model is similar to that designed by the constitutional legislator originating in the 1988 Constitution for health in Brazil. To distort the system completely, the legislature conveys different understanding to paragraph 2, art. 2 of the ordinary Law No. 8,080, of September 19, 1990, dividing the sole guarantor of duty in providing these public state health services to society, when in fact the Constitution, in Article 196 that highlights being the health, right of all and duty of the State. This breach of duty leads the population to pay for these services at your own risk entering into contracts directly with the private sector. To correct this inversion of values, the Judiciary works tirelessly in the effectiveness of the constitutional norm in health, and it is not seen in relation to other executive and legislative powers to the contrary, some are committed to public health, not giving priority and overseeing the public budget for that purpose, either by allowing health funds diversion to other areas, factors that reflect a low level of concern for the health, well-being and soon the life of its population. And therefore, it is allowed that the private insurance plans and health grow more and more, and in this case are the operators of health plans that dictate the rules in the consumer market, assuming the state a mere watchdog role number